SAT0146 Dissecting the Impact of Comorbidities on Disease Activity in Rheumatoid Arthritis: Ancillary Analysis from the COMORA Study. (10th June 2014) - Crepaldi, G.; Scirè, C.A.; Carrara, G.; Sakellariou, G.; Caporali, R.; Hmamouchi, I.; Dougados, M.; Montecucco, C.
Abstract : Background: Suppression of disease activity is the goal of the treatment of rheumatoid arthritis (RA). Therefore the use of validated composite measures of disease activity is needed in order to treat RA to target 1 . Objectives: To evaluate which comorbidities may influence each component of the clinical composite measures used to assess disease activity in RA. Methods: All RA patients enrolled in the international, cross-sectional study COMORA were eligible for the analyses. Collected data included demographics, disease characteristics and comorbidities (hypertension, diabetes, dyslipidemia, renal deficiency, ischemic heart disease, stroke, cancer, gastro-intestinal ulcers, hepatitis, depression, chronic pulmonary disease, obesity). Linear regression models explored the relationship between each comorbidity and the following disease activity measures: 28-swollen joint count (SJC), 28-tender joint count (TJC), erythrocyte sedimentation rate (ESR), patient's and physician's global assessment of disease (PtGA, PhGA), patient reported fatigue, functional disability (HAQ), DAS28 and CDAI. Results are presented as mean difference (MD). Results: A total of 3920 patients were included. Age (mean ± SD) 56.27±13.03 yrs, female 81.65%; disease duration median 7.08 yrs (IQR 2.97-13.27), DAS28 (mean ± SD) 3.74±1.55. Variations of the clinimetric indexes, in patients affected by considered comorbidities, are summarized in Table 1 . Conclusions: Diabetes and dyslipidemia seem to be associated with higher and lower disease activity respectively affecting almost all the variables considered. Other comorbidities influence single items suggesting a relationship with measure tools rather than with disease activity. Comorbidity specificities should be taken into account in the management of RA. References: Smolen JS et al. Treating rheumatoid arthritis to target: recommendations of an international task force. Ann Rheum Dis. 2010;69(4):631–7. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4388